Minor Head Injury Symptoms and Recovery From Whiplash Injury: A 1-Year Prospective Study. (April 2019) - Kasch, Helge; Jensen, Luana Leonora
Aim: To examine concussion-related disability in neck injuries, the Rivermead Head Injury Follow-Up Questionnaire (RHFUQ) was applied. Furthermore, we wanted to investigate symptoms found in post-concussion syndrome (PCS) and global pain, neck pain intensities obtained from acute whiplash patients within 1 week and at 6 months after injury in a prospective study on 1-year work disability. Methods: A total of 143 consecutive acute whiplash-injured patients were admitted to the study from the Emergency Unit (Aarhus University Hospital). Patients with direct head trauma or reported retro- or anterograde amnesia were excluded from the study. Average neck pain and global pain intensity were measured on a Visual Analogue Scale (VAS 0-10). The RHFUQ (10 items, score from 0 to 4, total score from 0 to 40) was fulfilled after 1 week and 6 months. Patients underwent neurological examination within 1 week after injury. Recovery (return to work) was assessed 1 year post-injury. Results: In total, 97% completed the study, and 9% (12/138) did not recover. Non-recovered patients reported more neck pain and global pain after 1 week ( P < .003) and 6 months ( P < .008) and higher PCS symptom score after 1 week ( P < .001) and 6 months ( P < .002). Using the RHFUQ total score as a predictive test, a receiver-operating characteristic curve (ROC) area of 0.77 (0.61-0.92) and a cut-off at 10 points revealed a sensitivity of 75% and a specificity of 67.2%. At 1 week, 8 of 10 items reached higher scores among non-recovered and 10 of 10 items after 6 months post-injury. Conclusions: RHFUQ is useful in acute whiplash patients for predicting 1-year work disability. PCS-related symptoms along with neck pain and global pain are more burdensome in the non-recovered group. This emphasizes that post-concussion symptoms are not a sign of brain injury alone, but are found in other types of mishaps like whiplash injuries.